Pelatihan Pembuatan Jala Tebar Modifikasi Sebagai Inovasi Alat Panen Udang bagi Desa Mitra â€œKampung Vanameâ€ Politeknik KP Jembrana Bali - Noar Muda Satyawan; Made Mahendra Jaya; Liya Tri Khikmawati; Wulandari Sarasati; Muth Mainnah; Yulia Estmirar Tanjov; Muh. Arkam Aziz; Iya Purnama Sari; Noveldesra Suhery; Rakhma Fitria Larasati (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service were to improve the skills of Partner Village "Kampung Vaname" cultivators in making modified Cast Net so as to minimize deaths that occur after partial harvest. The methods used in this service were socialization and training. The target of this service is the cultivator of Partner Village "Kampung Vaname" Marine and Fisheries Polytechnic of Jembrana. The service activity began with the presentation of the material then continued with training in making Cast Net. Evaluation were done by giving pre-test and post-test to all training participants. Based on the service results, there was an increase in the understanding of the farming group in Partner Village about fishing gear that could be applied in the vannamei shrimp cultivation process, the vannamei shrimp farming group in Partner Village was able to make modified Cast Net fishing gear properly, and modified of Cast Net fishing gear could be one of solution for solving the problem of vaname shrimp farmers related to partial post-harvest shrimp mortality.